EDUKASI PENCEGAHAN KESALAHAN MAKAN DAN MINUM PADA ORANG TUA ANAK DENGAN CEREBRAL PALSY - Hilmi Muhammad Ishak Hamdani; Muhamad Azmi Muzakki; Salwa Kanahaya Na’ila; Neny Widyana (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M), 2025)
Children with cerebral palsy often experience feeding and drinking difficulties due to impaired motor control and swallowing disorders. This condition increases the risk of choking and nutritional problems when parents lack adequate knowledge of safe feeding and drinking practices. This community service activity aimed to improve parents’ understanding and skills in preventing feeding and drinking errors in children with cerebral palsy by strengthening parents’ and caregivers’ knowledge and practical skills. The activity was conducted through lectures on feeding posture techniques, appropriate food texture selection, and recognition of feeding readiness signs, as well as demonstrations and guided practice of oral motor exercises focused on swallowing stimulation. The evaluation was carried out using pre-test and post test assessments involving 16 parents or caregivers of children with cerebral palsy. The results showed an increase in the mean knowledge score from 71.88 in the pre test to 90.63 in the post test. This community service activity contributes to supporting safer feeding and drinking practices for children with cerebral palsy.